Analisis Efektifitas Penyelesaian Tugas Akhir Mahasiswa (Studi pada Fakultas Ekonomi Universitas Lancang Kuning Pekanbaru) - waldelmi, idel (Jurnal Daya Saing, 2016)
Abstract: Faculty of economy consists of two major departments that are management and accounting. Study reveals that the level of end duty completion is quite effective around 58%. %. Study also reveals that each department has quite effective in assisting students to complete their end duty, i.e.: accounting 57.5% and management 52.2%. The effectiveness of student’s end duty completion are measured by input, process and output. The research is conducted by survey approach Keywords: Effectiveness, TAS